Establishing a vegetables crop with professional greenhouse - Alexandra-Marina Brătulescu (Agrarian Economy and Rural Development - Realities and Perspectives for Romania. 8th Edition of the International Symposium, November 2017, Bucharest, 2017)
Due to the changes that have taken place over the last period of time, at the level of the macromedium and micro-environment factors of an agricultural enterprise, the agricultural producer is challenged to have an activity characterized by performance and competitiveness. In order to support the needs of consumers of agri-food products, which suffer from many changes, it is important for the agricultural entity to obtain agricultural production at a higher quality level. This paper presents the stages of the establishment of a vegetable farm with professional solariums and greenhouses, having as main activity the tomato, pumpkin and spinach crops. During the paper, the elements of the micro-society (objectives, risks, market strategies), as well as elements of the macromedi (economic, technological, politico-legislative, natural) will be presented. It is also attempted to briefly present the aforementioned crop technology of vegetables. As a method of analysis, a feasibility study on setting up a vegetable farm will be presented in this paper, taking into account annual expenditure, estimated revenue, including estimated production costs. After analyzing all the elements presented, the section "Results and Discussions" presents the financial result and the recovery of the investment, taking a five-year horizon.
Keywords: L6; Q1; O5; 330; farm; feasibility study; spinach; pumpkin; tomatoes; solaria and greenhouses; vegetables